Peran Green Marketing dalam Meningkatkan Brand Loyalty: Studi pada Industri Makanan dan Minuman di Indonesia - Savandha, Septien Dwi (GEMA EKONOMI, 2024)
Increasing consumer awareness of environmental issues is driving companies to adopt green marketing strategies to strengthen their competitiveness. In the Indonesian food and beverage industry, green marketing practices are considered crucial due to the high consumption rate and significant contribution to environmental waste. This study aims to analyze the influence of green marketing dimensions (product, price, promotion, and distribution) on brand loyalty. The study employed a quantitative approach with a survey method involving 200 food and beverage consumer respondents who had purchased environmentally friendly products. The research instrument, a questionnaire with a five-point Likert scale, was tested for validity and reliability using Confirmatory Factor Analysis (CFA) and Cronbach's Alpha. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS software. The results showed that green product (β = 0.42, p < 0.001) and green promotion (β = 0.36, p < 0.001) had the largest significant influence on brand loyalty, while green price (β = 0.24, p < 0.05) and green distribution (β = 0.19, p < 0.05) also had significant but relatively weaker influence. The model explained 61.3% variance in brand loyalty. These findings confirm that Indonesian consumers prioritize the quality of environmentally friendly products and the authenticity of promotional communications over price. The implications emphasize the importance for food and beverage companies to strengthen sustainable product innovation, develop authentic marketing communications, and integrate green strategies into their business value chains to enhance consumer loyalty and contribute to sustainable development in Indonesia.